The Effect of Teaching A According To The Appleton Model In The Achievement of Biology Among Second –Year Intermediate Students (Journal of the College of Basic Education, 2024)
The aim of the research is to identify ( the effect of teaching according to the Appleton model in the achievement of biology among second-year intermediate students ) to verify the research objective the following null hypothesis was formulated : there is no statistically significant difference at level (0,05) between the average a achievement scores of students who study according to the Appleton model and the average scores of students who study according to the regular method , the research sample was determined by second-grade intermediate students at habib ullah middle school for boys affiliated with the Baghdad education directorate , al rusafa first , north Baghdad department. For the experimental group , the school was chosen intentionally the school includes (4) classes for the second intermediate grade , sections (a) and (b) were chosen randomly , and the research sample consisted of (93) students (46) students for the experimental group and (47) students for the control group the two groups were rewarded in testing some of the following variables : (previous information , previous achievement , and intelligence ) the scientific subject was defined in the first three chapters from the biology subject for the 5 nd edition of the year 2023 , behavioral objectives were formulated for the (162) chapters of the scientific subject according to blooms (levels of memory , comprehension , application , and analysis ) the experiment on Wednesday , corresponding to 8/11 /2023 , until Wednesday , corresponding to 10/ 1/ 2024 for the first semester of the academic year 2023- 2024 and the researcher constructed the achievement test for biology the standard characteristics and internal and external validity of the test were verified , and the following results were reached . the experimental group outperformed the control group with statistically significant difference in the biology achievement test . the researcher presented several recommendation and proposals .